Using the iPad to facilitate interaction between preschool children who use AAC and their peers. (2nd July 2016) - Therrien, Michelle C. S.; Light, Janice
Abstract: Social interaction is one of the key components of education, yet children with complex communication needs often face social isolation in the classroom, rarely interacting with same-age peers. This study investigated the impact of the provision of an iPad ® 1 with an AAC app with visual scene displays and a dyadic turn taking training on the number of communicative turns taken by children with complex communication needs in interaction with same-age peers. Two preschool children with complex communication needs and six peers without disabilities participated in this research. A single-subject, multiple probe across partners design with one replication was used to evaluate the effectiveness of the intervention on the frequency of communicative turns expressed by the children with complex communication needs. Parents, teachers, speech-language pathologists, and the children participated in social validation measures. As a result of intervention, Participant 1 showed immediate gains in the frequency of symbolic communicative turns after the first training session across all three partners (average gains of 30–46 symbolic communicative turns per 10-min session across peer partners). Participant 2 showed some initial gains, but they were not maintained over time (average gains of 11–24 turns across partners). Classroom implications and future research directions are discussed.